Pengaruh Capital Intensity, Kepemilikan Manajerial Dan Keragaman Gender Terhadap Tax Aggressiveness - Wulan Andriani; Jarno . (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to test and prove empirically the effect of Capital Intensity, Managerial Ownership, and Gender Diversity on Tax Aggressiveness. This research uses an associative quantitative approach. The data used is secondary data in the form of annual financial reports. The population of this study consisted of Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) consisting of 128 companies. The sample was taken using purposive sampling technique, resulting in a sample of 9 companies with observations for 5 years, resulting in a total of 45 audited annual financial reports. Data collection techniques in this study using documentation and literature study. The variables used in this study are Capital Intensity (X1), Managerial Ownership (X2), and Gender Diversity (X3) as independent variables and Tax Aggressiveness (Y) as the dependent variable. The tests used in this study are multiple regression analysis techniques, namely descriptive statistical tests, panel data regression model analysis, model selection tests, classical assumption tests, panel data regression analysis with linear equations and hypothesis testing with a significance level of 5%. Based on the results of hypothesis testing, it shows that capital intensity, managerial ownership, and gender diversity simultaneously have an influence on tax aggressiveness. Capital Intensity has no effect on tax aggressiveness, managerial ownership affects tax aggressiveness, and gender diversity affects tax aggressiveness.